2020
DOI: 10.1002/qua.26531
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies on how to tune the π‐hole pnicogen bonds by substitution and cooperative effects

Abstract: A systemic investigation of the substitution and cooperative effects on the P…N π‐hole pnicogen bond were performed via theoretical calculations. The structural and energetic properties of the binary complexes between a series of substituted benzonitrile and PO2F have been examined to study the substitution effect. The stability of the binary complexes increases in the order of CN < Br ≈ Cl < F < H < CH3 < NH2, in which all halogen atoms serve as the electron‐withdrawing substituents. The cooperativity between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…Although first-row N is quite reluctant to engage in σ-hole pnicogen bonds, it does so in the context of the π-hole above NFO 2 , with a strength of 5 kcal/mol. (Earlier sets of calculations , had evaluated the π-hole bond formed by the P-analogue PFO 2 , one of which provided an interaction energy with NH 3 of 35.5 kcal/mol.) ZnF 4 engages in a strong spodium bond with NH 3 , with E int equal to 30 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although first-row N is quite reluctant to engage in σ-hole pnicogen bonds, it does so in the context of the π-hole above NFO 2 , with a strength of 5 kcal/mol. (Earlier sets of calculations , had evaluated the π-hole bond formed by the P-analogue PFO 2 , one of which provided an interaction energy with NH 3 of 35.5 kcal/mol.) ZnF 4 engages in a strong spodium bond with NH 3 , with E int equal to 30 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…Although not as extensive as the research centering on σ-hole bonds, there has been substantial coverage of their π-hole cousins as well, particularly in the past few years. ,, This work has covered the full gamut of central atoms, from aerogen to pnicogen to triel bonds. In summary, it has been learned that π-hole bonds can be quite strong, competitive with their σ-hole bond sisters, and even stronger in some circumstances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have witnessed an explosive growth in the study of noncovalent bonds that are close parallels of the venerable H-bond. In each of the chalcogen, pnicogen, tetrel, and triel bonds, an atom of that same particular family of the periodic table replaces the bridging proton of the H-bond. Among these interactions, the halogen bond (XB) is arguably the one that has been acknowledged for the longest time and has engendered the greatest amount of scrutiny. Extensive study has demonstrated that the XB owes its stability to several factors. In the first place, the electron-density cloud surrounding the X atom is quite anisotropic; while the overall charge on the X atom is partially negative, there is a pocket of positive potential that lies along the extension of the covalent C–X bond, which is commonly referred to as a σ-hole.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the electron‐withdrawing O will enhance the lobe of the π* antibonding orbital that lies above the C atom, thereby facilitating charge transfer from the nucleophile in a direct parallel with σ‐hole bonding. Although the majority of the earlier studies of these sorts of noncovalent bonds were focused on σ‐hole bonds, there is a growing emphasis to better explore their π‐hole analogues 3,7,12,33–43 . While this work is continuing, it is important to stress here, that there are strong indications that π‐hole bonds are not necessarily weaker than their σ‐hole counterparts, and can indeed be stronger in numerous instances.…”
Section: Introductionmentioning
confidence: 97%